Assessment of current situation of medical education in the College of Medicine-University of Baghdad - Khattab, Omar S.; Tajer, Salah M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: The most important advances in medical education in the last decade are the shift in focus from learning objectives to learning outcomes. The advantages of active over passive learning are researched-based. The aim of this study was to evaluate the students reading habits; utilization of lectures, group study, resources utilized during study, and if there is a need to change the curriculum. Methods: A prospective study was done in Medical City Teaching Hospital, from January 2007 to January 2008, including 438 students from the college of medicine, university of Baghdad. A questionnaire consist of 28 questions was given to them. These questionnaire elicited responses regarding reading habits, utilization of lectures, group study, and resources utilized during study. The t-test was used for statistical analysis, the results were considered significant if P value < 0.05. Results: In this study students were dependant on passive learning mainly. There was greater use of the lecture notes, and less use of library, textbooks, Journals and online sources. The willing of the students to have active learning was significant (P value < 0.05) Conclusion: We would like to conclude that teaching methods are changing, and we should consider that in our curriculum, we should concentrate on active learning. There is a public expectation that we, in the academic and clinical community, will produce safe, ethical and professional doctors.